Seizures and brain regulatory systems: Consciousness, sleep, and autonomic systems - Sedigh-Sarvestani, Madineh (J Clin Neurophysiol, 2015)
Research into the physiological underpinnings of epilepsy has revealed reciprocal relationships between seizures and the activity of several regulatory systems in the brain, including those governing sleep, consciousness and autonomic functions. This review highlights recent progress in understanding and utilizing the relationships between seizures and the arousal or consciousness system, the sleep-wake and associated circadian system, and the central autonomic network.